NGAREKSAKEUN SASAKA PUSAKA BUANA: PANDANGAN ETIKA URANG KANEKES TENTANG HUBUNGAN MANUSIA DENGAN ALAM - Ulumi, Helmy Faizi Bahrul (Jurnal Filsafat "WISDOM", 2010)
AbstractThe environmental ethic of the Kanekes people lies in their world view of the navel of the universe (inti jagat), namely Sasaka Pusaka Buana which two primary events took place in a locality they refered to: the origin of the universe and the first humankind who was descended to the earth. The Kanekes people were entrusted to maintain the navel of the universe by a God (Batara Tunggal), and their ancestors (karuhun). Therefore within the moral system of the Kanekes People, the cosmos is regarded as a moral subject, like the human. The environmental ethic of the Kanekes people originatesÂ rom their philosophical views and culture, on which they establishes the foundations of their environmental ethic. Then from those bases, the Kanekes people formulates their environmental moral norms, which consist of proximate and ultimate norm. The proximate norms of their morality are their being congruent with the sacredness of the cosmos and Kanekes as the navel of the universe; their being congruent with the holiness of the human soul, which should be maintained; their being congruent with the tradition and the belief of their ancestors; the principles of modest life and the exploitation of things only when necessary. These proximate norms culminated to the ultimate norm which constitutesthe origin and the goal of mankind, i.e. God.Keywords: environmental ethic, ecology, Urang Kanekes, the navelof the universe, indigenous society, Sunda Wiwitan.